1996
DOI: 10.1212/wnl.46.5.1464
|View full text |Cite
|
Sign up to set email alerts
|

Tactile spatial acuity at the human fingertip and lip

Abstract: We used the spatial threshold for discrimination of grating orientation to assess tactile spatial acuity at the lower lip and each fingertip, bilaterally, in seven normal human subjects. We confirmed previous findings that: (1) this test is highly reliable, and (2) acuity at the lip is substantially higher than at the fingertips. In addition, we showed that: (1) acuity does not differ significantly between right and left sides, and (2) among fingertips, acuity is lowest at the fifth digit and comparable on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
66
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(85 citation statements)
references
References 3 publications
18
66
1
Order By: Relevance
“…We found further that acuity worsens from index to middle to ring fingertips, consistent with previous reports show- ing significant effects or trends in this direction (Sathian and Zangaladze, 1996;Vega-Bermudez and Johnson, 2001;Grant et al, 2006;Duncan and Boynton, 2007).…”
Section: Effects Of Test Site Sex and Agesupporting
confidence: 92%
See 1 more Smart Citation
“…We found further that acuity worsens from index to middle to ring fingertips, consistent with previous reports show- ing significant effects or trends in this direction (Sathian and Zangaladze, 1996;Vega-Bermudez and Johnson, 2001;Grant et al, 2006;Duncan and Boynton, 2007).…”
Section: Effects Of Test Site Sex and Agesupporting
confidence: 92%
“…As previously reported (Van Boven and Johnson, 1994;Sathian and Zangaladze, 1996), we found that acuity on the lips exceeds that on the fingertips. We found further that acuity worsens from index to middle to ring fingertips, consistent with previous reports show- ing significant effects or trends in this direction (Sathian and Zangaladze, 1996;Vega-Bermudez and Johnson, 2001;Grant et al, 2006;Duncan and Boynton, 2007).…”
Section: Effects Of Test Site Sex and Agesupporting
confidence: 89%
“…Return to normal performance on the GR/OR task closely paralleled the rate of reinnervation of the primary afferent fibers, as well as the subject's self-report of normal sensory function (Van Boven & Johnson, 1994b). The GR/OR task has also been used as a measure of spatial acuity at a number of different locations on the skin that are known to vary in their density of innervation (Craig, 1999;Craig & Kisner, 1998;Essock, Krebs, & Prather, 1997;Gibson & Craig, 2002;Patel, Essick, & Kelly, 1997;Sathian & Zangaladze, 1996;Van Boven & Johnson, 1994a). In each case, performance on the GR/OR task roughly correlated with changes in density of innervation of the primary afferent fibers.…”
mentioning
confidence: 82%
“…Several mechanisms have been proposed for tactile spatial acuity, including peripheral innervation density (Van Boven & Johnson, 1994), cortical magnification (Duncan & Boynton, 2007;Sathian & Zangaladze, 1996;Tegenthoff et al, 2005), and RF geometry in SI (Cody et al, 2008;Gibson & Craig, 2005). However, the relationship between measures of tactile spatial acuity and measures of Weber's illusion is not clear.…”
Section: Potential Neural Mechanisms Of Weber's Illusionmentioning
confidence: 99%